2016
DOI: 10.1177/0271678x16635657
|View full text |Cite
|
Sign up to set email alerts
|

Integrity of normal-appearing white matter: Influence of age, visible lesion burden and hypertension in patients with small-vessel disease

Abstract: White matter hyperintensities accumulate with age and occur in patients with stroke, but their pathogenesis is poorly understood. We measured multiple magnetic resonance imaging biomarkers of tissue integrity in normal-appearing white matter and white matter hyperintensities in patients with mild stroke, to improve understanding of white matter hyperintensities origins. We classified white matter into white matter hyperintensities and normal-appearing white matter and measured fractional anisotropy, mean diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
133
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(146 citation statements)
references
References 56 publications
(101 reference statements)
13
133
0
Order By: Relevance
“…While the tissue integrity of NAWM is negatively impacted by age and hypertension, no sex-specific differences have been reported to date. 13 Thus, our data suggest that white matter structural integrity may be a contributing variable on AIS functional outcomes in women.…”
Section: Discussionmentioning
confidence: 62%
“…While the tissue integrity of NAWM is negatively impacted by age and hypertension, no sex-specific differences have been reported to date. 13 Thus, our data suggest that white matter structural integrity may be a contributing variable on AIS functional outcomes in women.…”
Section: Discussionmentioning
confidence: 62%
“…Whereas there is evidence that MD is also more sensitive to age than FA among those with mild stroke48, our sample composition has implications for another aspect of our results. Whereas hippocampal volume and ICVF did not appear to provide unique information about age in this sample, both ICVF (rather than FA)49 and hippocampal volume50 are important dementia biomarkers, emphasizing that our findings, which focus on normal ageing, cannot necessarily be generalized to clinical populations.…”
Section: Discussionmentioning
confidence: 77%
“…6,28 A recent study of patients with mild ischemic stroke demonstrated that MD was the most sensitive metric for distinguishing WMH from NAWM and that the accumulation of interstitial fluid is involved in WMH pathogenesis. 17 Therefore, it is reasonable to assume that DTI-based anisotropy metrics of NAWM provide insights into WM composition and, as a result, are informative of functional connectivity and overall cognitive performance. 7,27,[29][30][31] Thus, it seems intuitive that WM integrity would influence poststroke recovery.…”
Section: Resultsmentioning
confidence: 99%
“…17 Because WM was defined on the basis of probability masks, no threshold values were used for extraction of the diffusivity anisotropy metrics in this analysis. Statistical analysis.…”
mentioning
confidence: 99%